PENGARUH KARAKTERISTIK KUAT TEKAN BETON MENGGUNAKAN SERBUK KAYU PADA CAMPURAN BETON - Sempurna Bangun; Kristina Sembiring (Jurnal Teknik, 2022)
Concrete is one of the fastest building materials in today's development. Developments in the development sector have triggered high demand which has an effect on increasing productivity in today's construction world, so that manufacturers want to create new innovations. Therefore, research related to efforts to improve concrete quality is necessary. The basic ingredients of concrete are cement, sand, gravel and water. This study uses the type of cement, namely the type of cement PCC (Portland Cement Composite) in a concrete mixture and its effect on the quality of the concrete. In the development of concrete, no research is often carried out on the use of sawdust for concrete. One of the sawdust that can be used as for concrete mixtures that are natural and environmentally friendly is sawdust. The purpose of this study was to determine the effect of adding sawdust. The time in this study for 35 days was tested for concrete aged 7, 28, and 35. In order to achieve the stated goals, this research has stages that must be carried out. The tests carried out were testing the constituent materials of concrete including fine aggregate and coarse aggregate, as well as testing the compressive strength of this study adding sawdust to the concrete mixture. From this study, the compressive strength value of the use of two types of cement is lower than normal concrete for the compressive strength value, for the strength value. The addition of sawdust increases the compressive strength and flexural strength values in concrete from the addition of 10% and 20% sawdust.